The efficacy of continuous ECG monitoring among low, intermediate, and high risk phase II cardiac rehabilitation patients - Grall, Sarah K. (My University, 1992)
Continuous electrocardiographic (CECG) monitoring is commonly used in Phase II cardiac rehabilitation programs to detect complications resulting from exercise. It has been suggested that high risk cardiac patients are more likely to experience a serious event during exercise sessions, and therefore should be monitored more closely. Stratifying risk implies that one can predict which patients are at an increased risk of experiencing complications during cardiac rehabilitation. To determine the usefulness of CECG and the application of risk stratification, a retrospective 5-year study of 241 Phase II patients was conducted. Risk stratification, based on AACVPR criteria resulted in 123 (51%) patients classified as low risk, 80 (33%) as intermediate risk, and 38 (16%) as high risk. The Phase I1 exercise records were examined to identify individuals who had a significant event during Phase II. All documented events which necessitated physician intervention or cessation of the exercise session were recorded. A total of 3,877 exercise sessions were reviewed. Ninety-nine significant events occurred in a total of 69 patients. Of the 99 total events, 57 (57%) were detected through the use of CECG. With regard to risk level, it was found that 29 (24%) low, 27 (34%) intermediate, and 13 (34%) high risk patients had at least one significant event. Chi-square analysis revealed no significant (p > .05) difference in the proportion of patients within each stratified subgroup who experienced events. Sixty six events occurred within the first 3 weeks of program initiation, with 75% being .detected through CECG. These results indicate that CECG may be efficatious for detecting abnormalities during Phase II cardiac rehabilitation, especially during the first 3 weeks of the program. Also, it appears that based on current risk stratification guidelines, it may be difficult to predict which patients will have complications during Phase II cardiac rehabilitation. The findings of this study may be helpful in formulating standardized monitoring guidelines for Phase II cardiac exercisers, and may also aid in revising current risk stratification procedures.
Keywords: Patient monitoring - Evaluation; Heart - Diseases - Patients - Rehabilitation; Ambulatory electrocardiography - Evaluation